Cotton packaging film with excellent toughness

By adopting a non-adhesive film of a specific configuration in the cotton packaging film, combined with the content of different types of polyethylene, the problem of longitudinal tearing of the cotton packaging film is solved, and the tear resistance and stability of the film are significantly improved.

CN119527711AActive Publication Date: 2025-02-28埃克森美孚(惠州)化工有限公司
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411713474.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Existing cotton packaging films are prone to longitudinal tearing during picking and packaging, which leads to the expansion of diaphragm cracks, affecting the use effect and equipment stability.

Method used

A non-adhesive film with an A/B/C/D/E configuration is adopted, wherein the A layer is in contact with the adhesive film and the E layer is in contact with cotton. Each layer contains a specific proportion of the first metallocene polyethylene, the second metallocene polyethylene, low-density polyethylene, high-density polyethylene and linear low-density polyethylene to improve the tear resistance of the film.

Benefits of technology

The longitudinal tear resistance of the cotton packaging film is significantly improved, the possibility of crack expansion is reduced, and the stability and service life of the film are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119527711A_ABST
    Figure CN119527711A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of packaging materials, in particular to a cotton packaging film with excellent toughness. Specifically, the present invention relates to a non-tacky film for a cotton baling film wherein the non-tacky film has a configuration of A / B / C / D / E, layer A is in contact with the tacky film and layer E is in contact with cotton wherein each of the layers A, B, C, D and E comprises a first metallocene polyethylene, a second metallocene polyethylene, a low density polyethylene, a high density polyethylene and / or a linear low density polyethylene. Excellent toughness and tear resistance are achieved by defining the specific content of the first metallocene polyethylene, the second metallocene polyethylene, the low-density polyethylene, the high-density polyethylene and the linear low-density polyethylene in the layers A, B, C, D and E and the combination of the first metallocene polyethylene, the second metallocene polyethylene, the low-density polyethylene, the high-density polyethylene and the linear low-density polyethylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, in particular to a cotton packaging film with excellent toughness. Background Art

[0002] Cotton is one of the most important crops in the world. Cotton baling film is mainly used to pack cotton. At present, cotton picking is mostly mechanized, for example, using cotton pickers. In order to prevent cotton from being contaminated again during the process of picking to the drying field, and to facilitate the subsequent transportation of cotton, these cotton pickers need cotton baling film to pack a large amount of cotton into a cylindrical shape.

[0003] Generally, cotton baling film includes non-sticky film and sticky film. During the operation of the cotton picker, the cotton is finally baled after being wound with a roll film. Each packaging section of the roll film wound on the reel includes a non-sticky film and a sticky film. When baling cotton, it is first wound with a non-sticky film; then with a sticky film, and the number of winding turns is determined according to the diameter of the cotton bale (usually 1-2 turns), and finally the cotton is baled.

[0004] Cotton baling film requires outstanding toughness, especially tear resistance, to prevent cracks from propagating during cotton picking and baling. TM XP 6026 is formulated for the production of high-end cotton baling film. However, longitudinal (MD) tearing has always been a pain point for end users: once the baling film is scratched or torn due to sharp branches or external forces in the cotton during the cotton picking and baling process, the cracks are likely to propagate along the longitudinal (MD) direction on the surface of the baling film. In addition, if a crack forms during the unwinding of the cotton baling film on the cotton picker, the crack will propagate along the longitudinal (MD) or transverse (TD) direction, which may cause the machine to jam or even stop, requiring the film roll to be reinstalled.

[0005] There is a need in the art for a cotton baling film having excellent toughness, particularly excellent tear resistance. Summary of the invention

[0006] Cotton baling films generally include sticky films and non-sticky films.

[0007] The present invention relates to a non-sticky film having excellent toughness, especially excellent tear resistance.

[0008] The tear resistance of a film can be characterized, for example, by Elmendorf tear resistance in the transverse (TD) and / or machine direction (MD). Compared to the transverse (TD) Elmendorf tear resistance, the machine direction (MD) Elmendorf tear resistance of a film is generally more difficult to improve.

[0009] The non-sticky film for cotton baling film disclosed in the present invention unexpectedly has excellent tear resistance, especially excellent tear resistance in the machine direction (MD).

[0010] Existing Exceed-based TM The non-adhesive film for cotton baling film of XP 6026 generally has a TD Elmendorf Tear of about 19.0 g / μm. However, the non-adhesive film for cotton baling film disclosed in the present invention has a TD Elmendorf Tear of greater than about 19.0 g / μm, such as greater than or equal to about 19.5 g / μm, such as greater than or equal to about 20.0 g / μm, such as greater than or equal to about 20.5 g / μm, such as greater than or equal to about 21.0 g / μm, such as greater than or equal to about 21.5 g / μm, such as greater than or equal to about 22.0 g / μm, such as greater than or equal to about 22.5 g / μm, such as greater than or equal to about 23.0 g / μm, such as greater than or equal to about 23.5 g / μm, such as greater than or equal to about 24.0 g / μm, wherein the TD Elmendorf Tear is determined according to the ASTM D1922-09 test method. The non-adhesive film for cotton baling film disclosed in the present invention has a TD Elmendorf Tear of less than or equal to about 25.0 g / μm, wherein the TD Elmendorf Tear is measured according to the ASTM D1922-09 test method. The explicitly disclosed range includes, but is not limited to, the range formed by any combination of the above-recited values, such as a TD Elmendorf Tear of greater than about 19.0 g / μm to about 25.0 g / μm, such as about 20.0 g / μm to about 25.0 g / μm.

[0011] Existing Exceed-based TMThe non-adhesive film for cotton baling film of XP 6026 generally has an MD Elmendorf Tear of about 5.0 g / μm. However, the non-adhesive film for cotton baling film disclosed in the present invention has an MD Elmendorf Tear of greater than about 5.0 g / μm, such as greater than or equal to about 5.5 g / μm, such as greater than or equal to about 6.0 g / μm, such as greater than or equal to about 6.1 g / μm, such as greater than or equal to about 6.5 g / μm, such as greater than or equal to about 7.0 g / μm, such as greater than or equal to about 8.0 g / μm, such as greater than or equal to about 9.0 g / μm, wherein the MD Elmendorf Tear is measured according to the ASTM D1922-09 test method. The non-adhesive film for cotton baling film disclosed in the present invention has an MD Elmendorf Tear of less than or equal to about 10.0 g / μm, wherein the MD Elmendorf Tear is measured according to the ASTM D1922-09 test method. Explicitly disclosed ranges include, but are not limited to, ranges formed by combining any of the above-recited numerical values, such as an MD Elmendorf Tear of greater than about 5.0 g / μm to 10.0 g / μm, such as about 5.5 g / μm to 10.0 g / μm.

[0012] According to an embodiment of the present invention, the present invention relates to a non-sticky film for cotton packaging film, wherein the cotton packaging film comprises a sticky film and a non-sticky film, wherein the non-sticky film has a configuration of A / B / C / D / E, the A layer contacts the sticky film and the E layer contacts the cotton,

[0013] wherein each of layers A, B, C, D and E comprises (or consists essentially of, or consists of) a first metallocene polyethylene, a second metallocene polyethylene, a low density polyethylene, a high density polyethylene and / or a linear low density polyethylene, wherein the first metallocene polyethylene is a BOCD polyethylene and the second metallocene polyethylene is not a BOCD polyethylene;

[0014] The first metallocene polyethylene and the second metallocene polyethylene are not present in layer A, the second metallocene polyethylene is present in each of layers B, D, and E at a level of at least about 60 weight percent, based on the weight of each of layers B, D, and E, and the second metallocene polyethylene is present in layer C at a level of at least about 20 weight percent, based on the weight of layer C,

[0015] The first metallocene polyethylene is present in an amount of about 10 wt % to about 25 wt % based on the total weight of the A, B, C, D, and E layers of the non-adhesive film.

[0016] The second metallocene polyethylene is present in an amount of about 40 wt % to about 65 wt % based on the total weight of the A, B, C, D, and E layers of the non-adhesive film.

[0017] Based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of the low-density polyethylene is about 10 wt % to about 20 wt %,

[0018] Based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of the high-density polyethylene is about 10 wt % to about 15 wt %,

[0019] The linear low density polyethylene is present in an amount of about 2 wt % to about 10 wt % based on the total weight of the A, B, C, D, and E layers of the non-adhesive film.

[0020] According to an embodiment of the present invention, the first metallocene polyethylene and the second metallocene polyethylene are not present in the A layer.

[0021] According to an embodiment of the present invention, the second metallocene polyethylene is present in each of the B, D, and E layers in an amount of at least about 60 weight %, such as at least about 65 weight %, such as at least about 70 weight %, such as at least about 75 weight %, based on the weight of each of the B, D, and E layers.

[0022] According to an embodiment of the present invention, the second metallocene polyethylene is present in the C layer in an amount of at least about 20 weight percent, such as at least about 25 weight percent, such as at least about 30 weight percent, such as at least about 35 weight percent, such as at least about 40 weight percent, based on the weight of the C layer.

[0023] According to an embodiment of the present invention, based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of the first metallocene polyethylene is about 10 wt% to about 25 wt%, such as about 13 wt%, such as about 15 wt%, such as about 20 wt%.

[0024] If the content of the first metallocene polyethylene in the non-sticky film is too low, the non-sticky film cannot achieve excellent tear resistance. If the content of the first metallocene polyethylene in the non-sticky film is too high, the non-sticky film is not stable enough during the blown film production process.

[0025] According to an embodiment of the present invention, based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of the second metallocene polyethylene is about 40 wt% to about 65 wt%, for example about 45 wt%, for example about 51 wt%, for example about 55 wt%, for example about 60 wt%.

[0026] According to an embodiment of the present invention, based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of low-density polyethylene is about 10 wt% to about 20 wt%, for example about 12 wt%, for example about 15 wt%, for example about 17 wt%, for example about 19 wt%.

[0027] According to an embodiment of the present invention, based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of high-density polyethylene is about 10 wt% to about 15 wt%, for example about 11 wt%, for example about 12 wt%, for example about 13 wt%, for example about 14 wt%.

[0028] According to an embodiment of the present invention, based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of the linear low-density polyethylene is about 2 wt% to about 10 wt%, for example about 4 wt%, for example about 6 wt%, for example about 7 wt%, for example about 9 wt%.

[0029] According to an embodiment of the present invention, the first metallocene polyethylene is a BOCD polyethylene, wherein the BOCD polyethylene contains from about 70 mol% to about 99 mol% of polymer units derived from ethylene, based on the total moles of polymer units of the BOCD polyethylene, and has a density of about 0.910 g / cm 3 About 0.920g / cm 3 , which is measured according to ASTM D-792 or ASTM D-1505, and melt index (MI, or I 2.16 ) is from about 0.1 g / 10 min to about 1.0 g / 10 min, as measured in accordance with ASTM D-1238-E (190° C. / 2.16 kg), and the first metallocene polyethylene has a composition distribution breadth index (CDBI) from about 20 wt % to about 55 wt %.

[0030] According to an embodiment of the present invention, the second metallocene polyethylene is not a BOCD polyethylene, the second metallocene polyethylene contains about 70 mol% to about 99 mol% of polymer units derived from ethylene, based on the total moles of polymer units of the second metallocene polyethylene, and a density of about 0.910 g / cm 3 About 0.920g / cm 3 , which is measured according to ASTM D-792 or ASTM D-1505, and melt index (MI, or I 2.16 ) is from about 0.1 g / 10 min to about 1.0 g / 10 min as measured in accordance with ASTM D-1238-E (190° C. / 2.16 kg), and wherein the second metallocene polyethylene has a composition distribution breadth index (CDBI) of >70 wt %.

[0031] According to an embodiment of the present invention, the low density polyethylene (LDPE) has a molecular weight of about 0.910 g / cm 3 To about 0.925g / cm 3 Density, which is measured according to ASTM D-792 or ASTM D-1505.

[0032] According to an embodiment of the present invention, the low density polyethylene (LDPE) has a melt index from greater than about 0.5 g / 10 min to less than about 2.0 g / 10 min, as measured according to ASTM D-1238-E (190° C. / 2.16 kg).

[0033] According to an embodiment of the present invention, the linear low density polyethylene (LLDPE) has a molecular weight of about 0.910 g / cm 3 To about 0.925g / cm 3 Density, which is measured according to ASTM D-792 or ASTM D-1505, where "linear" means that the polyethylene has no long chain branches or only a small amount of long chain branches.

[0034] According to an embodiment of the present invention, the linear low density polyethylene (LLDPE) has a melt index from greater than about 0.5 g / 10 min to less than about 2.0 g / 10 min, as measured according to ASTM D-1238-E (190° C. / 2.16 kg).

[0035] According to an embodiment of the present invention, the high density polyethylene (HDPE) has a density greater than about 0.950 g / cm 3 The density of the composite is measured according to ASTM D-792 or ASTM D-1505.

[0036] According to an embodiment of the present invention, the high density polyethylene (HDPE) has a melt index from greater than about 0.5 g / 10 min to less than about 2.0 g / 10 min, as measured according to ASTM D-1238-E (190° C. / 2.16 kg).

[0037] According to an embodiment of the present invention, the present invention provides a non-sticky film for cotton packaging film, wherein the cotton packaging film comprises a sticky film and a non-sticky film, wherein the non-sticky film has a configuration of A / B / C / D / E, the A layer contacts the sticky film and the E layer contacts the cotton,

[0038] wherein each of A, B, C, D and E comprises a first metallocene polyethylene, a second metallocene polyethylene, a low density polyethylene, a high density polyethylene and / or a linear low density polyethylene, wherein the first metallocene polyethylene is a BOCD polyethylene and the second metallocene polyethylene is not a BOCD polyethylene;

[0039] The first metallocene polyethylene and the second metallocene polyethylene are not present in layer A, the second metallocene polyethylene is present in each of layers B, D, and E at a level of at least about 60 weight percent, based on the weight of each of layers B, D, and E, and the second metallocene polyethylene is present in layer C at a level of at least about 20 weight percent, based on the weight of layer C,

[0040] The first metallocene polyethylene is present in an amount of about 10 wt% to about 25 wt% based on the total weight of the A, B, C, D, and E layers of the non-stick film, wherein the first metallocene polyethylene contains about 70 mol% to about 99 mol% of polymer units derived from ethylene, based on the total moles of polymer units of the first metallocene polyethylene, and has a density of about 0.914 g / cm 3 , which is measured according to ASTM D-792, and melt index (MI, or I 2.16 ) is about 0.80 g / 10 min, which is measured according to ASTM D-1238-E (190° C. / 2.16 kg), and the first metallocene polyethylene has a composition distribution breadth index (CDBI) of about 43 wt %,

[0041] The second metallocene polyethylene is present in an amount of about 40 wt% to about 65 wt% based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, wherein the second metallocene polyethylene contains about 70 mol% to about 99 mol% of polymer units derived from ethylene, based on the total moles of polymer units of the second metallocene polyethylene, and has a density of about 0.916 g / cm 3 , which is measured according to ASTM D-792, and melt index (MI, or I 2.16 ) is about 0.20 g / 10 min, which is measured according to ASTM D-1238-E (190° C. / 2.16 kg), and the second metallocene polyethylene has a composition distribution breadth index (CDBI) of about 80 wt %,

[0042] Based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of low-density polyethylene is about 10 wt% to about 20 wt%, wherein the low-density polyethylene (LDPE) has a viscosity of about 0.923 g / cm 3 A density of 0.75 g / 10 min, measured according to ASTM D-1238-E (190° C. / 2.16 kg),

[0043] Based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of high-density polyethylene is about 10 wt% to about 15 wt%, wherein the high-density polyethylene (HDPE) has a viscosity of 0.961 g / cm 3 A density of about 0.70 g / 10 min, as measured according to ASTM D-1238-E (190° C. / 2.16 kg), and

[0044] Based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of the linear low-density polyethylene is about 2 wt% to about 10 wt%, wherein the linear low-density polyethylene (LLDPE) has a viscosity of about 0.918 g / cm 3 The polyurethane has a density of about 1.0 g / 10 min, as measured according to ASTM D-1238-E (190° C. / 2.16 kg).

[0045] The thickness of the non-adhesive film of the present invention may be a common thickness in the art. According to an embodiment of the present invention, the non-adhesive film of the present invention may have a total thickness of 65.0-80.0 μm, for example 75.0 μm.

[0046] According to an embodiment of the present invention, the non-adhesive film of the present invention has a configuration of A / B / C / D / E, wherein the thickness ratio of each layer A:B:C:D:E can be 1:b:c:d:1, wherein b is a number from 2 to 3, c is a number from 2 to 4, and d is a number from 2 to 3; the thickness ratio of each layer A:B:C:D:E is based on the thickness of the A layer or the E layer (i.e., the thickness of the A layer and the E layer is fixed to 1).

[0047] For example, for the non-adhesive film of the present invention, the thickness ratio of each layer A:B:C:D:E may be 1:2:3:3:1.

[0048] Metallocene polyethylene (mPE)

[0049] According to an embodiment of the present invention, the non-sticky film for cotton baling film comprises a first metallocene polyethylene and a second metallocene polyethylene, wherein the metallocene polyethylene is a polyethylene homopolymer or a polyethylene copolymer prepared using a metallocene catalyst.

[0050] As used herein, the term "metallocene catalyst" is defined as comprising at least one transition metal compound containing one or more substituted or unsubstituted cyclopentadienyl moieties (Cp) (typically two Cp moieties) together with a transition metal from Group 4, 5 or 6 of the Periodic Table of the Elements such as zirconium, hafnium and titanium.

[0051] "Metallocene catalysts" generally need to be activated with a suitable cocatalyst or activator to produce an "active metallocene catalyst", i.e., an organic metal complex having vacant coordination sites that can coordinate, insert and polymerize olefins. Active catalyst systems generally include not only metallocene complexes, but also activators, such as aluminoxanes or derivatives thereof (preferably methylaluminoxane), ionizing activators, Lewis acids or combinations thereof. Alkylaluminoxanes (generally methylaluminoxane and modified methylaluminoxane) are particularly suitable as catalyst activators. The catalyst system can be supported on a carrier, which is generally an inorganic oxide or chloride or a resin material, such as polyethylene or silica.

[0052] The first metallocene polyethylene

[0053] According to an embodiment of the present invention, a non-stick film for cotton baling film comprises a first metallocene polyethylene and a second metallocene polyethylene, wherein the first metallocene polyethylene is a broad orthogonal composition distribution (BOCD) polyethylene.

[0054] Broad orthogonal composition distribution (BOCD) polyethylene is a polyethylene homopolymer or a polyethylene copolymer, in most cases a polyethylene copolymer. It is desirable that the polyethylene has a broad orthogonal composition distribution that provides an enhanced balance of stiffness, toughness, and processability (S / T / P) for polyethylene and compositions comprising these polymers. Considering that a polymer is a blend of molecules with different chain length distributions, a polymer with BOCD is a branched polymer having any branching that occurs, predominantly if not entirely, on the high molecular weight molecules of the polymer, which makes them less crystalline. This microstructure has a tendency to improve certain properties of products made from the BOCD-type polymers (including the polyolefin compositions described herein).

[0055] Ziegler-Natta ("ZN") produced polyethylenes tend not to have a BOCD type structure, with most short chain branching occurring on the low molecular weight portion of the molecules so produced. On the other hand, some metallocene polyethylenes can often have a BOCD type structure. The value of BOCD polymers relative to conventional polymers is significant.

[0056] In embodiments of the present invention, the BOCD polyethylene may have a "broad orthogonal composition distribution" ("BOCD"). The broad orthogonal composition distribution may be determined using a fractionation technique, such as gel permeation chromatography-differential viscometer (GPC-DV), temperature rising elution fractionation-differential viscometer (TREF-DV), or a cross-fractionation technique. For example, WO 2015 / 123164A1 (which is incorporated herein by reference) discusses the TREF technique, providing a measurement of the bivariate mass distribution of the crystalline portion of a BOCD polyethylene.

[0057] The BOCD polyethylene of the present invention comprises about 70 mol% to about 99 mol% of units derived from ethylene, based on the total moles of polymer units of the BOCD polyethylene. Based on the total moles of polymer units of the BOCD polyethylene, the lower limit of the content range of units derived from ethylene can be 70 mol%, 75 mol%, 80 mol%, 85 mol%, 90 mol%, 92 mol%, 94 mol%, 95 mol%, 96 mol%, 97 mol%, 98 mol% or 99 mol%. Based on the total moles of polymer units of the BOCD polyethylene, the upper limit of the content range of units derived from ethylene can be 80 mol%, 85 mol%, 90 mol%, 92 mol%, 94 mol%, 95 mol%, 96 mol%, 97 mol%, 98 mol%, 99 mol%. Any of the above upper limit contents can be combined with any of the above upper limit contents; any of the above upper limit contents can be combined with any of the above lower limit contents; and any of the above upper limit contents can be combined with any of the above lower limit contents.

[0058] The BOCD polyethylene of the present invention may have equal to or less than 30 mol% of polymer units derived from C3-C20 olefins, such as C3-C20 α-olefins, such as hexene or octene. Based on the total moles of polymer units of the BOCD polyethylene, the upper limit of the content range of polymer units derived from C3-C20 olefins may be 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 8 mol%, 6 mol%, 5 mol%, 4 mol%, 3 mol%, 2 mol%, 1 mol% or 0.5 mol%. Based on the total moles of polymer units of the BOCD polyethylene, the lower limit of the content range of polymer units derived from C3-C20 olefins may be 0 mol%, 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol%, 8 mol%, 10 mol%, 15 mol%, 20 mol% or 25 mol%. Any of the above upper limits may be combined with any of the above upper limits; any of the above upper limits may be combined with any of the above lower limits; and any of the above upper limits may be combined with any of the above lower limits.

[0059] According to an embodiment of the present invention, the density of the BOCD polyethylene measured according to ASTM D-792 or ASTM D-1505 may be ≥ about 0.910 g / cm 3 , for example ≥ about 0.911 g / cm 3 , for example ≥ about 0.912 g / cm 3 , for example ≥ about 0.913 g / cm 3 , for example ≥ about 0.914 g / cm3 , for example ≥ about 0.915 g / cm 3 , for example ≥ about 0.916 g / cm 3 , for example ≥ about 0.917 g / cm 3 , for example ≥ about 0.918 g / cm 3 , for example ≥ about 0.919 g / cm 3 density.

[0060] Additionally or alternatively, the BOCD polyethylene may have a density of ≤ about 0.920 g / cm2 as measured according to ASTM D-792 or ASTM D-1505. 3 , for example ≤ about 0.919 g / cm 3 , for example ≤ about 0.918 g / cm 3 , for example ≤ about 0.917 g / cm 3 , for example ≤ about 0.916 g / cm 3 , for example ≤ about 0.915 g / cm 3 , for example ≤ about 0.914 g / cm 3 , for example ≤ about 0.913 g / cm 3 The explicitly disclosed ranges include, but are not limited to, the ranges formed by any combination of the above-listed values, such as about 0.910 g / cm 3 -About 0.920g / cm 3 , about 0.913g / cm 3 -About 0.920g / cm 3 , about 0.914g / cm 3 - About 0.918g / cm 3 , about 0.915g / cm 3 - About 0.917g / cm 3 wait.

[0061] According to an embodiment of the present invention, the melt index (MI, or I 2.16 ) can be ≥ about 0.1 g / 10 min, for example ≥ about 0.2 g / 10 min, for example ≥ about 0.3 g / 10 min, for example ≥ about 0.4 g / 10 min, for example ≥ about 0.5 g / 10 min, for example ≥ about 0.6 g / 10 min, for example ≥ about 0.7 g / 10 min, for example ≥ about 0.8 g / 10 min, for example ≥ about 0.9 g / 10 min.

[0062] Additionally or alternatively, the BOCD polyethylene may have a melt index (MI, or I 2.16) can be ≤ about 1.0 g / 10 min, such as ≤ about 0.9 g / 10 min, such as ≤ about 0.8 g / 10 min, such as ≤ about 0.7 g / 10 min, such as ≤ about 0.6 g / 10 min, such as ≤ about 0.5 g / 10 min, such as ≤ about 0.4 g / 10 min, such as ≤ about 0.3 g / 10 min. The explicitly disclosed range includes, but is not limited to, the range formed by any combination of the above-listed values, such as about 0.1 g / 10 min to about 1.0 g / 10 min, such as about 0.2 g / 10 min to about 0.9 g / 10 min.

[0063] The term "Composition Distribution Breadth Index (CDBI)" represents the weight percent of copolymer molecules having a comonomer content within 50% of the median molar content of all comonomers. The BOCD polyethylenes of the present invention typically have a broad composition distribution as measured by the Composition Distribution Breadth Index (CDBI).

[0064] The CDBI of a copolymer can be measured using techniques known in the art. The CDBI of a copolymer is easily determined using well-known techniques for isolating individual fractions of a copolymer sample. One such technique is temperature rising elution fractionation (TREF), as described in Wild et al., J. Poly. Sci., Poly. Phys. Ed., Vol. 20, pp. 441-455 (1982), which is incorporated herein by reference. Generally, a high CDBI indicates that most components are washed out in a shorter period of time (smaller temperature range) and the comonomer distribution is narrow; a low CDBI indicates that most components are washed out in a longer period of time (larger temperature range), indicating that the comonomer distribution is wide.

[0065] Details on determining the CDBI of a copolymer are known to those skilled in the art, for example, see PCT patent application WO 1993 / 003093 published on February 18, 1993 (which is incorporated herein by reference), the content regarding CDBI in the specification, such as the fourth paragraph on page 13 of the specification, the transition paragraph on pages 14-15, the transition paragraph on pages 18-19, etc.

[0066] According to an embodiment of the present invention, the BOCD polyethylene is characterized in that it has a composition distribution breadth index (CDBI) from about 20 wt % to about 55 wt %. For example, the composition distribution breadth index (CDBI) of the BOCD polyethylene can be ≥ about 20 wt %, such as ≥ about 25 wt %, such as ≥ about 30 wt %, such as ≥ about 40 wt %, such as ≥ about 43 wt %, such as ≥ about 45 wt %, such as ≥ about 50 wt %, such as ≥ about 52 wt %.

[0067] Additionally or alternatively, the composition distribution breadth index (CDBI) of the BOCD polyethylene can be ≤ about 55 wt %, such as ≤ about 53 wt %, such as ≤ about 50 wt %, such as ≤ about 45 wt %, such as ≤ about 40 wt %, such as ≤ about 35 wt %, such as ≤ about 30 wt %, such as ≤ about 25 wt %. Explicitly disclosed ranges include, but are not limited to, ranges formed by any combination of the above-listed values, such as from about 20 wt % to about 55 wt %, such as from about 30 wt % to about 50 wt %, such as from about 35 wt % to about 50 wt %, etc.

[0068] Materials and methods for making BOCD polyethylene have been described in, for example, U.S. Patent No. 6,956,088, particularly Example 1; U.S. Patent Application Publication No. 2009 / 0297810, particularly Example 1; U.S. Patent Application Publication No. 2015 / 0291748, particularly PE1-PE5 in the examples; and WO 2014 / 099356, particularly PE3 mentioned on page 12 and in the examples, including the use of silica-supported hafnium transition metallocene / methylaluminoxane catalyst systems such as described in U.S. Patent Nos. 6,242,545 and 6,248,845 (particularly Example 1).

[0069] Many BOCD polyethylenes are commercially available. One or more BOCD polyethylenes are commercially available from ExxonMobil Chemical Company, Houston, TX, and as Exceed TM XP metallocene polyethylene (mPE) sales. Exceed TM XPmPE offers advantageous properties such as dart impact strength, flex crack resistance and machine direction (MD) tear, as well as maintaining stiffness at lower density. TM XP mPE also offers a good balance of melt strength, toughness, stiffness and sealing ability, which makes this class of polymers well suited for example for blown film.

[0070] In the present embodiment, the following BOCD polyethylene is used as the first metallocene polyethylene:

[0071] Exceed TM XP 8784 is a polyethylene available from ExxonMobil Chemical Company, Houston, TX, which is a copolymer of ethylene and 1-hexene having a molecular weight of 0.914 g / cm2 as measured according to ASTM D792. 3and a melt index of 0.80 g / 10 min measured according to ASTM D1238 (190° C. / 2.16 kg), and a composition distribution breadth index (CDBI) of about 43 wt %.

[0072] The second metallocene polyethylene

[0073] According to an embodiment of the present invention, a non-stick film for cotton baling film comprises a first metallocene polyethylene and a second metallocene polyethylene, wherein the second metallocene polyethylene is not a broad orthogonal composition distribution (BOCD) polyethylene.

[0074] According to an embodiment of the present invention, a metallocene polyethylene having a CDBI>70 wt% is defined as not being a broad orthogonal composition distribution (BOCD) polyethylene.

[0075] According to an embodiment of the present invention, the second metallocene polyethylene has a composition distribution width index (CDBI) of>70 weight %. The second metallocene polyethylene of the present invention comprises about 70mol% to about 99mol% of units derived from ethylene, based on the total moles of the polymer units of the second metallocene polyethylene. Based on the total moles of the polymer units of the second metallocene polyethylene, the lower limit of the content range of the units derived from ethylene can be 70mol%, 75mol%, 80mol%, 85mol%, 90mol%, 92mol%, 94mol%, 95mol%, 96mol%, 97mol%, 98mol% or 99mol%. Based on the total moles of the polymer units of the second metallocene polyethylene, the upper limit of the content range of the units derived from ethylene can be 80mol%, 85mol%, 90mol%, 92mol%, 94mol%, 95mol%, 96mol%, 97mol%, 98mol%, or 99mol%. Any of the above upper limits may be combined with any of the above upper limits; any of the above upper limits may be combined with any of the above lower limits; and any of the above upper limits may be combined with any of the above lower limits.

[0076] The second metallocene polyethylene of the present invention can have equal to or less than 30mol% of polymer units derived from C3-C20 olefins, such as C3-C20 alpha-olefins, such as hexene or octene. Based on the total moles of the polymer units of the second metallocene polyethylene, the upper limit of the content range of the polymer units derived from C3-C20 olefins can be 30mol%, 25mol%, 20mol%, 15mol%, 10mol%, 8mol%, 6mol%, 5mol%, 4mol%, 3mol%, 2mol%, 1mol% or 0.5mol%. Based on the total moles of the polymer units of the second metallocene polyethylene, the lower limit of the content range of the polymer units derived from C3-C20 olefins can be 0mol%, 1mol%, 2mol%, 3mol%, 4mol%, 5mol%, 6mol%, 8mol%, 10mol%, 15mol%, 20mol% or 25mol%. Any of the above upper limits may be combined with any of the above upper limits; any of the above upper limits may be combined with any of the above lower limits; and any of the above upper limits may be combined with any of the above lower limits.

[0077] According to an embodiment of the present invention, the density of the second metallocene polyethylene measured according to ASTM D-792 or ASTM D-1505 may be ≥ about 0.910 g / cm 3 , for example ≥ about 0.911 g / cm 3 , for example ≥ about 0.912 g / cm 3 , for example ≥ about 0.913 g / cm 3 , for example ≥ about 0.914 g / cm 3 , for example ≥ about 0.915 g / cm 3 , for example ≥ about 0.916 g / cm 3 , for example ≥ about 0.917 g / cm 3 , for example ≥ about 0.918 g / cm 3 , for example ≥ about 0.919 g / cm 3 density.

[0078] Additionally or alternatively, the second metallocene polyethylene may have a density of ≤ about 0.920 g / cm2 as measured according to ASTM D-792 or ASTM D-1505. 3 , for example ≤ about 0.919 g / cm 3 , for example ≤ about 0.918 g / cm 3 , for example ≤ about 0.917 g / cm 3 , for example ≤ about 0.916 g / cm 3 , for example ≤ about 0.915 g / cm 3, for example ≤ about 0.914 g / cm 3 , for example ≤ about 0.913 g / cm 3 The explicitly disclosed ranges include, but are not limited to, the ranges formed by any combination of the above-listed values, such as about 0.910 g / cm 3 -About 0.920g / cm 3 , about 0.913g / cm 3 -About 0.920g / cm 3 , about 0.914g / cm 3 - About 0.918g / cm 3 , about 0.915g / cm 3 - About 0.917g / cm 3 wait.

[0079] According to an embodiment of the present invention, the melt index (MI, or I 2.16 ) can be ≥ about 0.1 g / 10 min, for example ≥ about 0.2 g / 10 min, for example ≥ about 0.3 g / 10 min, for example ≥ about 0.4 g / 10 min, for example ≥ about 0.5 g / 10 min, for example ≥ about 0.6 g / 10 min, for example ≥ about 0.7 g / 10 min, for example ≥ about 0.8 g / 10 min, for example ≥ about 0.9 g / 10 min.

[0080] Additionally or alternatively, the second metallocene polyethylene has a melt index (MI, or I 2.16 ) can be ≤ about 1.0 g / 10 min, such as ≤ about 0.9 g / 10 min, such as ≤ about 0.8 g / 10 min, such as ≤ about 0.7 g / 10 min, such as ≤ about 0.6 g / 10 min, such as ≤ about 0.5 g / 10 min, such as ≤ about 0.4 g / 10 min, such as ≤ about 0.3 g / 10 min. The explicitly disclosed range includes, but is not limited to, the range formed by any combination of the above-listed values, such as about 0.1 g / 10 min to about 1.0 g / 10 min, such as about 0.2 g / 10 min to about 0.9 g / 10 min.

[0081] The second metallocene polyethylene is commercially available from ExxonMobil Chemical Company, Houston, TX, and is marketed as Exceed TM XP metallocene polyethylene (mPE) sales. Exceed TMXP mPE offers advantageous properties such as dart impact strength, flex crack resistance and machine direction (MD) tear as well as maintaining stiffness at lower density. TM XP mPE also offers a good balance of melt strength, toughness, stiffness and sealing ability, which makes this class of polymers well suited for example for blown film.

[0082] The following second metallocene polyethylene is used in the embodiments of the present invention:

[0083] Exceed TM XP 6026 is a polyethylene available from ExxonMobil Chemical Company, Houston, TX, which is a copolymer of ethylene and 1-hexene with a molecular weight of 0.916 g / cm2 as measured according to ASTM D792. 3 Density and melt index of 0.20 g / 10 min measured according to ASTM D1238 (190°C / 2.16 kg). TM XP 6026 has a composition distribution breadth index (CDBI) of approximately 80 wt%.

[0084] Low-density polyethylene (LDPE)

[0085] According to an embodiment of the present invention, the non-sticky film for cotton baling film further comprises low-density polyethylene (LDPE) in addition to the first metallocene polyethylene and the second metallocene polyethylene.

[0086] It is well known in the art that low density polyethylene (LDPE) typically has a branching index (g') <1.

[0087] According to an embodiment of the present invention, a density of about 0.910 g / cm 3 To about 0.925g / cm 3 Polyethylene with a density of 1000 Nm is called low density polyethylene (LDPE) and is measured according to ASTM D-792 or ASTM D-1505.

[0088] According to an embodiment of the present invention, the lower limit of the density of the low-density polyethylene (LDPE) may be about 0.910 g / cm 3 , for example, about 0.912 g / cm 3 , for example, about 0.914 g / cm 3 , for example, about 0.916 g / cm 3 , for example, about 0.918 g / cm 3 , for example, about 0.920 g / cm 3 , for example, about 0.922 g / cm 3 , for example, about 0.923 g / cm 3, for example, about 0.924 g / cm 3 Etc., measured according to ASTM D-792 or ASTM D-1505.

[0089] According to an embodiment of the present invention, the upper limit of the density of the low-density polyethylene (LDPE) may be about 0.925 g / cm 3 , for example, about 0.924 g / cm 3 , for example, about 0.923 g / cm 3 , for example, about 0.922 g / cm 3 , for example, about 0.920 g / cm 3 , for example, about 0.918 g / cm 3 , for example, about 0.916 g / cm 3 , for example, about 0.914 g / cm 3 , for example, about 0.912 g / cm 3 Etc., as measured according to ASTM D-792 or ASTM D- 1505. Explicitly disclosed ranges include, but are not limited to, ranges formed by combining any of the above-recited numerical values.

[0090] According to an embodiment of the present invention, the low density polyethylene (LDPE) has a melt index of from greater than about 0.5 g / 10 min to less than about 2.0 g / 10 min, measured according to ASTM D-1238-E (190°C / 2.16 kg), such as about 0.6 g / 10 min, such as about 0.7 g / 10 min, such as about 0.8 g / 10 min, such as about 0.9 g / 10 min, such as about 1.0 g / 10 min, such as about 1.2 g / 10 min, such as about 1.5 g / 10 min, such as about 1.7 g / 10 min, etc. The explicitly disclosed range includes, but is not limited to, the range formed by any combination of the above-recited values.

[0091] Low density polyethylene (LDPE) useful in the present invention is available from a variety of sources, for example, the LD series low density polyethylene from ExxonMobil Chemical Company, Houston, TX.

[0092] In the embodiments of the present invention, ExxonMobil TM LDPE LD150 was used as the low density polyethylene, which was purchased from ExxonMobil Chemical Company, Houston, TX.

[0093] ExxonMobil TM LDPE LD150 has the following performance parameters:

[0094] Density: 0.923g / cm 3 , which is measured according to ASTM D-1505;

[0095] Melt index: 0.75 g / 10 min, which is measured according to ASTM D-1238-E (190° C. / 2.16 kg).

[0096] Linear Low Density Polyethylene (LLDPE)

[0097] According to an embodiment of the present invention, the non-sticky film for cotton baling film further comprises a linear low density polyethylene (LLDPE) in addition to the first metallocene polyethylene and the second metallocene polyethylene.

[0098] According to an embodiment of the present invention, a density of about 0.910 g / cm 3 To about 0.925g / cm 3 Linear polyethylene of 100% to 100% is called linear low density polyethylene (LLDPE), where the density is measured according to ASTM D-792 or ASTM D-1505, where "linear" means that the polyethylene has no long chain branches or only a small amount of long chain branches. It is well known in the art that linear low density polyethylene (LLDPE) generally has a branching index (g') of about 1.

[0099] According to an embodiment of the present invention, the lower limit of the density of the linear low-density polyethylene (LLDPE) may be about 0.910 g / cm 3 , for example, about 0.912 g / cm 3 , for example, about 0.914 g / cm 3 , for example, about 0.916 g / cm 3 , for example, about 0.918 g / cm 3 , for example, about 0.920 g / cm 3 , for example, about 0.922 g / cm 3 , for example, about 0.923 g / cm 3 , for example, about 0.924 g / cm 3 Etc., measured according to ASTM D-792 or ASTM D-1505.

[0100] According to an embodiment of the present invention, the upper limit of the density of the linear low-density polyethylene (LLDPE) may be about 0.925 g / cm 3 , for example, about 0.924 g / cm 3 , for example, about 0.923 g / cm 3 , for example, about 0.922 g / cm 3 , for example, about 0.920 g / cm 3 , for example, about 0.918 g / cm 3, for example, about 0.916 g / cm 3 , for example, about 0.914 g / cm 3 , for example, about 0.912 g / cm 3 Etc., as measured according to ASTM D-792 or ASTM D- 1505. Explicitly disclosed ranges include, but are not limited to, ranges formed by combining any of the above-recited numerical values.

[0101] According to an embodiment of the present invention, the linear low density polyethylene (LLDPE) has a melt index of from greater than about 0.5 g / 10 min to less than about 2.0 g / 10 min, measured according to ASTM D-1238-E (190°C / 2.16 kg), such as about 0.6 g / 10 min, such as about 0.7 g / 10 min, such as about 0.8 g / 10 min, such as about 0.9 g / 10 min, such as about 1.0 g / 10 min, such as about 1.2 g / 10 min, such as about 1.5 g / 10 min, such as about 1.7 g / 10 min, etc. The explicitly disclosed range includes, but is not limited to, the range formed by any combination of the above-recited values.

[0102] Linear low density polyethylene (LLDPE) useful in the present invention is available from a variety of sources, for example, the LL series linear low density polyethylene from ExxonMobil Chemical Company, Houston, TX.

[0103] In the embodiments of the present invention, ExxonMobil TM LLDPE LL 1001AV was used as the linear low density polyethylene, which was purchased from ExxonMobil Chemical Company, Houston, TX.

[0104] ExxonMobil TM LLDPE LL 1001AV has the following performance parameters:

[0105] Density: 0.918g / cm 3 , which is measured according to ASTM D792;

[0106] Melt index: 1.0 g / 10 min, which is measured according to ASTM D-1238-E (190° C. / 2.16 kg).

[0107] High-density polyethylene (HDPE)

[0108] According to an embodiment of the present invention, the non-sticky film for cotton baling film further comprises high-density polyethylene (HDPE) in addition to the first metallocene polyethylene and the second metallocene polyethylene.

[0109] According to the common definition in the art, a density greater than about 0.950 g / cm 3 Ethylene polymers of ethylene are referred to as "high density polyethylene (HDPE)" where the density is measured according to ASTM D-792 or ASTM D-1505.

[0110] According to an embodiment of the present invention, the density of high-density polyethylene (HDPE) may be greater than 0.950 g / cm 3 , for example ≥ about 0.960 g / cm 3 wait.

[0111] According to an embodiment of the present invention, the high density polyethylene (HDPE) has a melt index of from greater than about 0.5 g / 10 min to less than about 2.0 g / 10 min, measured according to ASTM D-1238-E (190°C / 2.16 kg), such as about 0.6 g / 10 min, such as about 0.7 g / 10 min, such as about 0.8 g / 10 min, such as about 0.9 g / 10 min, such as about 1.0 g / 10 min, such as about 1.2 g / 10 min, such as about 1.5 g / 10 min, such as about 1.7 g / 10 min, etc. The explicitly disclosed range includes, but is not limited to, the range formed by any combination of the above-recited values.

[0112] High density polyethylene (HDPE) useful in the present invention is available from a variety of sources, for example, the HTA series of high density polyethylenes from ExxonMobil Chemical Company, Houston, TX.

[0113] In the embodiments of the present invention, ExxonMobil TM HDPE HTA 108 was used as high density polyethylene, which was purchased from ExxonMobil Chemical Company, Houston, TX.

[0114] ExxonMobil TM HDPE HTA 108 has the following performance parameters:

[0115] Density: 0.961g / cm 3 , measured according to ASTM D-1505;

[0116] Melt index: 0.70 g / 10 min, which is measured according to ASTM D-1238-E (190° C. / 2.16 kg).

[0117] Film production method

[0118] The non-adhesive film for cotton baling film of the present invention is produced by a blown film process well known in the art.

[0119] The composition is extruded in a molten state through an annular die, and then expanded to form a uniaxial or biaxially oriented melt. It is then cooled to form a tubular blown film. It can then be axially cut and expanded to form a flat film. The film can then be unoriented, uniaxially oriented, or biaxially oriented to the same or different extents.

[0120] According to an embodiment of the present invention, a non-adhesive film is first produced by a blown film line, and then an adhesive film is produced by a blown film line. Afterwards, the non-adhesive film and the adhesive film are combined together. BRIEF DESCRIPTION OF THE DRAWINGS

[0121] Figure 1 The structure of a cotton baling film is exemplified, which includes a non-adhesive film and an adhesive film.

[0122] Figure 2 The figure shows the comparison of various properties of the non-sticky film produced in the embodiment of the present invention and the non-sticky film of the comparative example, wherein the solid line represents the non-sticky film produced in the embodiment of the present invention and the dotted line represents the non-sticky film of the comparative example. DETAILED DESCRIPTION

[0123] In order to better understand the technical solution of the present invention, the applicant provides the following examples for illustration. The examples are only for the purpose of illustration and do not limit the scope of protection of the present invention.

[0124] Measurement method

[0125] The present invention uses the following measurement method.

[0126] Table 1

[0127] Measurement method TD Elmendorf tear (g / μm) ASTM D1922-09 MD Elmendorf tear (g / μm) ASTM D1922-09 MD 1% secant modulus (MPa) ASTM D-882 MD tensile strength at break (N) ASTM D-882 MD elongation at break (%) ASTM D-882

[0128] Example

[0129] According to the composition shown in Table 2, a non-sticky film for cotton bale film having an A / B / C / D / E configuration was produced on a blown film line, wherein the total thickness of the 5-layer non-sticky film was about 75.0 μm, and the thickness ratio of each layer A:B:C:D:E was 1:2:3:3:1.

[0130] The present invention uses the following raw materials:

[0131] The first metallocene polyethylene: Exceed TM XP 8784, indicated by "8784" in Table 2;

[0132] The second metallocene polyethylene: Exceed TMXP 6026, indicated by "6026" in Table 2;

[0133] Low-density polyethylene: ExxonMobil TM LDPE LD150, indicated by "LDPE" in Table 2;

[0134] Linear low density polyethylene: ExxonMobil TM LLDPE LL 1001AV, denoted as “LLDPE” in Table 2;

[0135] High-density polyethylene: ExxonMobil TM HDPE HTA 108, denoted as "HDPE" in Table 2.

[0136] In Table 2, the content (expressed in weight %) in each layer A / B / C / D / E is based on the total weight of the corresponding layer, for example, based on the weight of the A, B, C, D or E layer, respectively.

[0137] In Table 2, "Dosage" indicates the content (expressed in weight %) of 6026, 8784, LDPE, LLDPE and HDPE, respectively, based on the total weight of the 5-layer non-adhesive film.

[0138] Table 2

[0139] layer A B C D E dose 6026 70% by weight 30 wt% 70% by weight 70% by weight 51% by weight LDPE 60% by weight 10 wt% 20% by weight 10 wt% 17 wt% HDPE 40 wt% 12 wt% LLDPE 40 wt% 10% by weight 7% by weight 8784 20% by weight 20% by weight 30 wt% 13 wt%

[0140] The properties of the non-adhesive film produced in the embodiment of the present invention and the non-adhesive film of the comparative example are shown in Table 3, wherein the non-adhesive film of the comparative example is commercially available, and the manufacturer is Changzhou Kaide New Material Technology Co., Ltd. The non-adhesive film of the comparative example also has a thickness of about 75.0 μm, which is based on Exceed TM The non-sticky film of the comparative example does not contain the Exceed XP 6026 used in the present invention. TM XP 8784.

[0141] The content of the metallocene polyethylene in the comparative example ranges from about 61 wt % to about 65 wt % based on the total weight of the non-stick film.

[0142] The content of metallocene polyethylene in the embodiment of the present invention is about 64% by weight, that is, Exceed TM XP 6026 content +Exceed TM XP 8784 content (51 wt% + 13 wt%).

[0143] Table 3

[0144] Non-adhesive film according to an embodiment of the present invention Non-sticky film of comparative example TD Elmendorf tear (g / μm) 20.5 19.1 MD Elmendorf tear (g / μm) 6.1 5.1 MD 1% secant modulus (MPa) 340 367 MD tensile strength at break (N) 39.9 37.5 MD elongation at break (%) 627 624

[0145] It can be seen from Table 3 that the non-adhesive film of the present invention has an MD Elmendorf tear of up to 6.1 g / μm, which shows that the non-adhesive film of the present invention has excellent MD tear resistance. Compared with the non-adhesive film of the comparative example, the non-adhesive film of the present invention has an MD Elmendorf tear increased by 19.6%.

[0146] Furthermore, the non-adhesive film of the present invention has a TD Elmendorf tear of 20.5 g / μm, indicating that the non-adhesive film of the present invention has excellent TD tear resistance. Compared with the non-adhesive film of the comparative example, the non-adhesive film of the present invention has a TD Elmendorf tear improved by 7.3%.

[0147] In addition, from the present invention Figure 2 It can be seen that compared with the non-adhesive film of the comparative example, the non-adhesive film of the present invention performs better in the following five aspects: TD Elmendorf tear, MD Elmendorf tear, MD 1% secant modulus, MD tensile strength at break, and MD elongation at break.

[0148] In particular, the non-sticky film of the present invention has significantly improved MD Elmendorf tear compared to the non-sticky film of the comparative example, which indicates that the non-sticky film of the present invention has excellent MD tear resistance.

[0149] All documents described herein, including any priority documents and / or test procedures are introduced for reference under all jurisdictions that do not conflict with the present invention. It is obvious from the above overview and specific embodiments that, although the form of the present disclosure has been illustrated and described, various modifications can be made without departing from the spirit and scope of the present disclosure. Therefore, it is not desired that the present disclosure be limited in this way. Similarly, the term "comprising" is considered to be synonymous with the term "including". Similarly, whenever a composition, element or element group is in front of the transitional term "comprising", it should be understood that it is also considered to have the transitional term "essentially consisting of", "consisting of", "selected from" or "being" in front of the listed composition, element or each element The same composition or element group, and vice versa.

[0150] For simplicity, only some numerical ranges are clearly disclosed herein. However, a certain lower limit can be used in combination with any other upper limit to limit the scope that is not clearly recorded. Similarly, a certain lower limit can be used in combination with any other lower limit to limit the scope that is not clearly recorded. Similarly, a certain upper limit can also be used in combination with any upper limit to limit the scope that is not clearly recorded. In addition, even if there is no clear description, each point or individual value between the two end points is also included in the scope. Therefore, each point or individual value itself can be used as a lower limit or upper limit in combination with other points or individual values ​​or other lower or upper limits to limit the scope that is not clearly recorded.

Claims

1. A non-sticky film for cotton packaging film, wherein the cotton packaging film comprises a sticky film and a non-sticky film, wherein the non-sticky film has a configuration of A / B / C / D / E, the A layer contacts the sticky film and the E layer contacts the cotton, wherein each of A, B, C, D and E comprises a first metallocene polyethylene, a second metallocene polyethylene, a low density polyethylene, a high density polyethylene and / or a linear low density polyethylene, wherein the first metallocene polyethylene is a BOCD polyethylene and the second metallocene polyethylene is not a BOCD polyethylene; The first metallocene polyethylene and the second metallocene polyethylene are not present in layer A, the second metallocene polyethylene is present in each of layers B, D, and E at a level of at least about 60 weight percent, based on the weight of each of layers B, D, and E, and the second metallocene polyethylene is present in layer C at a level of at least about 20 weight percent, based on the weight of layer C, The first metallocene polyethylene is present in an amount of about 10 wt% to about 25 wt% based on the total weight of the A, B, C, D, and E layers of the non-stick film, wherein the first metallocene polyethylene contains about 70 mol% to about 99 mol% of polymer units derived from ethylene, based on the total moles of polymer units of the first metallocene polyethylene, and has a density of about 0.910 g / cm 3 To about 0.920g / cm 3 , which is measured according to ASTM D-792 or ASTM D-1505, and melt index (MI, or I 2.16 ) is from about 0.1 g / 10 min to about 1.0 g / 10 min, as measured in accordance with ASTM D-1238-E (190° C. / 2.16 kg), and the first metallocene polyethylene has a composition distribution breadth index (CDBI) from about 20 wt % to about 55 wt %, The second metallocene polyethylene is present in an amount of about 40 wt% to about 65 wt% based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, wherein the second metallocene polyethylene contains about 70 mol% to about 99 mol% of polymer units derived from ethylene, based on the total moles of polymer units of the second metallocene polyethylene, and has a density of about 0.910 g / cm 3 To about 0.920g / cm 3 , which is measured according to ASTM D-792 or ASTM D-1505, and melt index (MI, or I 2.16 ) is from about 0.1 g / 10 min to about 1.0 g / 10 min, as measured in accordance with ASTM D-1238-E (190° C. / 2.16 kg), and the second metallocene polyethylene has a composition distribution breadth index (CDBI) of >70 wt %, Based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of the low-density polyethylene is about 10 wt % to about 20 wt %, The high density polyethylene is present in an amount of about 10 wt % to about 15 wt % based on the total weight of the A, B, C, D, E layers of the non-adhesive film, and The linear low density polyethylene is present in an amount of about 2 wt % to about 10 wt % based on the total weight of the A, B, C, D, and E layers of the non-adhesive film.

2. The non-stick film according to claim 1, wherein the low density polyethylene (LDPE) has a viscosity of about 0.910 g / cm 3 To about 0.925g / cm 3 Density, as measured according to ASTM D-792 or ASTM D-1505, and having a melt index from greater than about 0.5 g / 10 min to less than about 2.0 g / 10 min, as measured according to ASTM D-1238-E (190° C. / 2.16 kg).

3. The non-stick film according to any one of claims 1 to 2, wherein the linear low density polyethylene (LLDPE) has a viscosity of about 0.910 g / cm 3 To about 0.925g / cm 3 Density, as measured according to ASTM D-792 or ASTM D-1505, and having a melt index from greater than about 0.5 g / 10 min to less than about 2.0 g / 10 min, as measured according to ASTM D-1238-E (190° C. / 2.16 kg).

4. The non-stick film according to any one of claims 1 to 3, wherein the high density polyethylene (HDPE) has a viscosity greater than about 0.950 g / cm 3 The present invention relates to a polyurethane elastomer having a density of 0.5 g / 10 min to 1.5 g / 10 min as measured in accordance with ASTM D-792 or ASTM D-1505, and a melt index of from greater than about 0.5 g / 10 min to less than about 2.0 g / 10 min as measured in accordance with ASTM D-1238-E (190° C. / 2.16 kg).

5. The non-stick film according to any one of claims 1 to 4, wherein the non-stick film has a TD Elmendorf Tear of greater than about 19.0 g / μm to about 25.0 g / μm, wherein the TD Elmendorf Tear is determined according to ASTM D1922-09 test method.

6. The non-stick film according to any one of claims 1 to 5, wherein the non-stick film has a MD Elmendorf Tear of greater than about 5.0 g / μm to about 10.0 g / μm, wherein the MD Elmendorf Tear is determined according to ASTM D1922-09 test method.

7. A non-sticky film for cotton packaging film, wherein the cotton packaging film comprises a sticky film and a non-sticky film, wherein the non-sticky film has a configuration of A / B / C / D / E, the A layer contacts the sticky film and the E layer contacts the cotton, wherein each of A, B, C, D and E comprises a first metallocene polyethylene, a second metallocene polyethylene, a low density polyethylene, a high density polyethylene and / or a linear low density polyethylene, wherein the first metallocene polyethylene is a BOCD polyethylene and the second metallocene polyethylene is not a BOCD polyethylene; The first metallocene polyethylene and the second metallocene polyethylene are not present in layer A, the second metallocene polyethylene is present in each of layers B, D, and E at a level of at least about 60 weight percent, based on the weight of each of layers B, D, and E, and the second metallocene polyethylene is present in layer C at a level of at least about 20 weight percent, based on the weight of layer C, The first metallocene polyethylene is present in an amount of about 10 wt% to about 25 wt% based on the total weight of the A, B, C, D, and E layers of the non-stick film, wherein the first metallocene polyethylene contains about 70 mol% to about 99 mol% of polymer units derived from ethylene, based on the total moles of polymer units of the first metallocene polyethylene, and has a density of about 0.914 g / cm 3 , which is measured according to ASTM D-792, and melt index (MI, or I 2.16 ) is about 0.80 g / 10 min, which is measured according to ASTM D-1238-E (190° C. / 2.16 kg), and the first metallocene polyethylene has a composition distribution breadth index (CDBI) of about 43 wt %, The second metallocene polyethylene is present in an amount of about 40 wt% to about 65 wt% based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, wherein the second metallocene polyethylene contains about 70 mol% to about 99 mol% of polymer units derived from ethylene, based on the total moles of polymer units of the second metallocene polyethylene, and has a density of about 0.916 g / cm 3 , which is measured according to ASTM D-792, and melt index (MI, or I 2.16 ) is about 0.20 g / 10 min, which is measured according to ASTM D-1238-E (190° C. / 2.16 kg), and the second metallocene polyethylene has a composition distribution breadth index (CDBI) of about 80 wt %, Based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of low-density polyethylene is about 10 wt% to about 20 wt%, wherein the low-density polyethylene (LDPE) has a viscosity of about 0.923 g / cm 3 A density of 0.75 g / 10 min, measured according to ASTM D-1238-E (190° C. / 2.16 kg), Based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of high-density polyethylene is about 10 wt% to about 15 wt%, wherein the high-density polyethylene (HDPE) has a viscosity of 0.961 g / cm 3 A density of about 0.70 g / 10 min, as measured according to ASTM D-1238-E (190° C. / 2.16 kg), and Based on the total weight of the A, B, C, D, and E layers of the non-adhesive film, the content of the linear low-density polyethylene is about 2 wt% to about 10 wt%, wherein the linear low-density polyethylene (LLDPE) has a viscosity of about 0.918 g / cm 3 The polyurethane has a density of about 1.0 g / 10 min, as measured according to ASTM D-1238-E (190° C. / 2.16 kg).

8. The non-adhesive film according to claim 7, wherein the non-adhesive film has a TD Elmendorf Tear of greater than about 19.0 g / μm to about 25.0 g / μm, wherein the TD Elmendorf Tear is determined according to ASTM D1922-09 test method.

9. The non-stick film according to any one of claims 7-8, wherein the non-stick film has a MD Elmendorf Tear of greater than about 5.0 g / μm to about 10.0 g / μm, wherein the MD Elmendorf Tear is determined according to ASTM D1922-09 test method.

10. A cotton baling film comprising the non-sticky film according to any one of claims 1 to 9.

11. A process for producing a non-sticky film according to any one of claims 1 to 9, which is produced by a blown film process.

Citation Information

Patent Citations

  • Polyethylene Films and Process for Production Thereof

    US20090297810A1

  • Films Comprising Ethylene-Based Polymers and Methods of Making Same

    US20150291748A1

  • Polymerization catalyst systems comprising substituted hafnocenes

    US6248845B1

  • Polyethylene films with improved physical properties

    US6956088B2

  • Heat sealed article

    WO1993003093A1